Water quality assessment of small water supply reservoir using statistical and analytical methods - Gonzalez, Nicolas A., author; Swain, N. R., author; Obregon, O., author; Williams, G. P., author; Nelson, E. J., author; Eggett, Dennis L., author; Colorado State University, publisher (Colorado State University. Libraries, 2012)
We evaluated twenty-eight years (1980-2007) of spatial-temporal water quality data from Deer Creek reservoir in Utah. The data came from three sampling points representing the lotic, transitional and lentic zones and included measurements of climatological, hydrological, and surface water quality conditions. The time frame spanned dates before and after the completion of the Jordanelle Reservoir (1987-1992), approximately fourteen miles upstream of Deer Creek. Our analysis showed changed conditions in Deer Creek prior to dam construction. On average chlorophyll-a and phosphorus levels have dropped since 1984 while dissolved oxygen levels have remained steady. We evaluated temporal groupings and found that a traditional month distribution following standard seasons was not effective in characterizing the measured conditions; we developed a more representative seasonal grouping by performing a Tukey-Kramer multiple comparison adjustment. Based on this analysis, we determined the best groupings were Cold (December - April), Transition (May and November) and Warm (June - October). We used Analyses of variance (ANOVA) calculations to determine if the temporal and spatial variations were statistically different. We found significant spatial variation in chlorophyll-a and nutrients. In general values were higher in the lotic zone than the lentic zone. We performed a principal component analysis (PCA) to determine principal parameters associated with the water quality of the reservoir which confirmed our seasonal groups showing the Cold, Transition and Warm seasons as separate.
Hydrology days 2012
AGU hydrology days 2012
2012 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2012.